Bioautography‐guided HPTLC–MS as a rapid hyphenated technique for the identification of antimicrobial compounds from selected South African Combretaceae species. Issue 8 (10th August 2022) - Anokwuru, Chinedu P.; Chen, Weiyang; van Vuuren, Sandy; Combrinck, Sandra; Viljoen, Alvaro M.
Abstract: Introduction: Many species within Combretaceae are traditionally used for the treatment of bacterial infections. The similarity in chemistry and antimicrobial activities within the family pose a challenge in selecting suitable species for herbal drug development. Objective: This study aimed at rapidly identifying antimicrobial compounds using bioautography‐guided high‐performance thin‐layer chromatography coupled with mass spectrometry (HPTLC–MS). Methods: Hierarchical cluster analysis of ultra‐performance liquid chromatography‐mass spectrometry data from the methanol extracts of 77 samples, representing four genera within Combretaceae, was carried out. Based on groupings on the dendrogram, 15 samples were selected for bioautography analysis against four pathogens ( Staphylococcus aureus, Bacillus cereus, Escherichia coli and Salmonella typhimurium ). Active compounds were identified using HPTLC–MS analysis of bands corresponding to the inhibition zones. Results: Bioautography revealed 15 inhibition zones against the four pathogens, with the most prominent present for Combretum imberbe . Analysis of the active bands, using HPTLC–MS indicated that flavonoids, triterpenoids and combretastatin B5 contributed to the antibacterial activity. The compounds corresponding to molecular ions m/z 471 ( Combretum imberbe ) and 499 ( Combretum elaeagnoides ) inhibited all four pathogens, and were identified as imberbic acid and jessic acid, respectively. Chemotaxonomic analysis indicated that arjunic acid, ursolic acid and an unidentified triterpenoid ( m/z 471) were ubiquitous in the Combretaceae species and could be responsible for their antibacterial activities. Conclusion: Application of HPTLC–MS enabled the rapid screening of extracts to identify active compounds within taxonomically related species. This approach allows for greater efficiency in the natural product research workflow to identify bioactive compounds in crude extracts. Abstract : This study was aimed at rapidly identifying antimicrobial compounds within Combretaceae using bioautography‐guided high‐performance thin‐layer chromatography‐mass spectrometry (HPTLC‐MS). Representative samples were subjected to bioautography against bacterial pathogens, and compounds were identified from the active bands using HPTLC‐MS. Chemotaxonomic analysis revealed that arjunic acid, ursolic acid, and an incompletely identified triterpenoid (m/z 471) were ubiquitous in the Combretaceae species and associated with antibacterial activity. This approach enables rapid extract screening to identify active compounds within taxonomically related species.